O Online Single Submission (OSS) menjadi gerbang pengajuan perizinan usaha dan pelayanan usaha mikro kecil secara sederhana - Fajar, Osama Malik (Maliki Interdisciplinary Journal, 2024)
Contracts are a vital element in the law regulating agreements between parties. This article outlines the various forms of contract and the evidentiary powers associated with each. Oral contracts, written contracts in private deeds, and written contracts in authentic deeds are three forms of contracts that are often encountered in legal practice. Oral contracts, although valid in some situations, are often susceptible to misinterpretation. Written contracts in private deeds provide stronger written evidence, but still require additional evidence in court. Meanwhile, contracts in authentic deeds provide stronger evidentiary power and greater legal protection. Choosing the right form of contract has important implications in the case of legal disputes, and a good understanding of the various forms of contract and their evidentiary power is key to maintaining the enforceability and validity of legal agreements.